2004
DOI: 10.1097/01.pgp.0000130108.03231.89
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Staining for p16 and p53 in Premalignant and Malignant Epithelial Lesions of the Vulva

Abstract: Two distinct types of vulvar squamous cell carcinomas and their precursors, vulvar intraepithelial neoplasias (VIN), which differ in terms of clinical presentation and behavior, have been delineated. Human papillomavirus (HPV)-associated carcinomas are of basaloid or warty type, whereas tumors unrelated to HPV are usually keratinizing and differentiated. Thus, the major stratifying factor for vulvar carcinomas and VIN is their etiopathogenetic relationship with HPV. However, because of technical difficulties i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
81
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(94 citation statements)
references
References 29 publications
11
81
1
1
Order By: Relevance
“…However, in their series of 10 cases with verrucous carcinoma, Gaulco et al, found that all the cases were found to be HPV negative in in-situ DNA hybridization analysis performed by HPV 6/11, 16/18, 31/35/51 probes [17]. In addition, Santos et al, supported the study of Gaulco et al, by their studies stating that p53 was negative in all the verrucous carcinoma cases [11,17]. In our study, in contrast to the studies mentioned above, p53 showed low grade positivity (1+), but in accordance with the cases in literature, Ki-67 proliferation index was rather low (6%) and p16 was negative.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…However, in their series of 10 cases with verrucous carcinoma, Gaulco et al, found that all the cases were found to be HPV negative in in-situ DNA hybridization analysis performed by HPV 6/11, 16/18, 31/35/51 probes [17]. In addition, Santos et al, supported the study of Gaulco et al, by their studies stating that p53 was negative in all the verrucous carcinoma cases [11,17]. In our study, in contrast to the studies mentioned above, p53 showed low grade positivity (1+), but in accordance with the cases in literature, Ki-67 proliferation index was rather low (6%) and p16 was negative.…”
Section: Discussionsupporting
confidence: 67%
“…The patients in this group typically develop a conventional (keratinizing) type ISCC associated with lichen sclerosis (LS) and squamous hyperplasia (SCH), and recent studies have shown the relationship with differentiated (simplex) VIN. Moreover, mutation in p53 tumor suppressing gene has often been observed [1,2,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…One study (Conscience et al, 2006), reported that p16 overexpression was significantly observed in 58% of cutaneous carcinomas (SCC:60% and BCC:50%) versus 0% of normal human skin. In another study (Santos et al, 2004), p16 was positive in 60% of BCCs and 91% in keratinizing SCC.…”
Section: Discussionmentioning
confidence: 99%
“…Full or near full thickness p16 INK4A immunostaining characterizes most classic VINs, but normal and hyperplastic vulvar epidermis, lichen sclerosus, and differentiated VIN are usually p16 negative. 17,18 Presence of strongly p53-positive suprabasal cells was proposed as an aid for the diagnosis of differentiated VIN 20 but this marker is not considered highly sensitive. Independent studies found a range of 54 to 83% of differentiated VINs to have abnormal p53 immunostaining patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical analysis for abnormal patterns of p16 INK4A , p53, and MIB1/Ki-67 expression, separately or as a panel, can distinguish classic from differentiated VIN but these markers often fail to identify the latter. [17][18][19][20] We therefore sought to find a more reliable biomarker for differentiated VIN.…”
mentioning
confidence: 99%